Penggunaan Metode Card Sort untuk Meningkatkan Hasil Belajar Siswa Kelas V UPT SPF SDN 106155 Tandem Hilir 1 - Masyitha, Siti; Malinda, Leni; Ramadhan, Nuri (Medan Resource Center, 2024)
This study addresses the issue of low learning outcomes among fifth-grade students at UPT SPF SDN 106155 Tandem Hilir 1, as reflected in the first semester's daily tests, where only 40% of students met the criteria for passing. The low performance, particularly in social studies, was attributed to teacher-centered instruction and limited use of diverse teaching methods. The research aimed to improve these learning outcomes by implementing the card sort method. Utilizing a classroom action research (CAR) design, the study involved 25 fifth-grade students and was conducted over two cycles. Each cycle consisted of planning, implementation, observation, and reflection. Data were collected through observation, student outcome tests, and documentation and analyzed using both qualitative and quantitative methods. The findings revealed that the application of the card sort method significantly improved student performance, with an increase in the average completion rate from 52% (average score 46.6) in cycle I to 88.8% (average score 80) in cycle II, marking a 36.8% improvement. The study concludes that the card sort method effectively enhances social studies learning outcomes in the target class.